Groundwater irrigation in Bangladesh: changing modalities, resultant policies - Banerjee, Anurag; Ray, Shreya; Chakraborty, Shreya; Mukherji, Aditi (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2022)
International Water Management Institute (IWMI) brought together in collaboration the CGIAR initiative “Transforming Agrifood Systems in South Asia” (TAFSSA), the “Solar Irrigation for Agricultural Resilience” (SoLAR) project, funded by the Swiss Agency for Development and Cooperation (SDC) and CGIAR initiative MITIGATE+ for organizing a national stakeholder workshop in Bangladesh in partnership with the Infrastructure Development Company Limited (IDCOL) and NGO Forum. The aim was to facilitate deliberations and develop a better understanding of challenges such as replacing diesel with solar irrigation pumps, the consequences of rapid electrification on the groundwater market, and the threat to groundwater sustainability posed by cheaper irrigation. Based on this the workshop envisages strengthening the policy research on the challenges and opportunities of Bangladesh's evolving groundwater irrigation sector.